Fatal Toxoplasma gondii COUG strain infections in southern sea otters (Enhydra lutris nereis): New insight on contributing factors and parasite serotyping - Devinn M. Sinnott; Melissa Miller; David Arranz-Solís; Felipe Rodriguez; Jeroen P. J. Saeij; Francesca Batac; Katherine Greenwald; Colleen Young; Michael D. Harris; Mary Gomes; Karen Shapiro (PLoS ONE, 2025)
Fatal infections with the rare COUG strain of the zoonotic parasite Toxoplasma gondii were recently detected for the first time in four southern sea otters (Enhydra lutris nereis) exhibiting severe protozoal steatitis. The objectives of this study were to describe new COUG strain infections in sea otters, investigate the potential contributory role of a recently discovered parasite-infecting narnavirus (Apocryptovirus odysseus) in these infections, assess the potential contribution of vitamin E deficiency in the development of systemic steatitis, and explore the utility of serotyping for strain-specific diagnosis of T. gondii infections in sea otters. Since initial reporting, six additional sea otters died due to fatal COUG strain T. gondii infections. Five animals exhibited lesion patterns resembling the prior case definition including severe, widespread steatitis. The final case died due to severe T. gondii-associated meningoencephalitis with no grossly or microscopically apparent steatitis. In contrast with a recent report utilizing a cougar-derived parasite isolate, A. odysseus RNA was not detected in sea otter-derived COUG strain isolates, suggesting that this narnavirus is not associated with fatal COUG strain infections in sea otters. Serotyping using dense granule (GRA) peptides to distinguish between T. gondii strains infecting sea otters suggests that Type X, Type II, and COUG strains exhibit different peptide-reactivity profiles that may allow them to be distinguished serologically. COUG strain T. gondii infections are an emerging threat to southern sea otter population health, and this strain has the potential to infect other animal and human hosts that share their environment and food sources with sea otters. Additional studies are needed to clarify the environmental sources, epidemiology, pathophysiology, and premortem serodiagnosis of COUG strain T. gondii infections in southern sea otters and other susceptible hosts.